Rhizoremediation activities of Vigna unguiculata (L.) in lead polluted soil under Rhizobium-symbiotic intervention - Ilara-Mokin (Journal of Pure and Applied Agriculture, 2023)
Potentials of Cowpea (Vigna unguiculata) to bio accumulate Lead (Pb) from soil after treatment with poultry manure were assessed to provide phytoremediation of Pb pollutant in contaminated soil. Soil samples were spiked at lead concentrations of 0 mg kg -1 Pb, 250 mg kg-1 Pb, 50mg kg-1 Pb, 750 mg kg -1 Pb and 1000 mg kg-1 Pb in a completely randomised design with poultry manure added at 0.0 g kg-1 and 12.5 g kg-1 . The setup was simulated thrice. Values of soil parameters were obtained using standard methods. At 12 weeks, the concentrations of lead were assessed in soil and plants using analytical methods. Data obtained were analyzed statistically using descriptive and inferential models. The mean concentrations of Pb in Vigna unguiculata treated with poultry manure were approximately 4-folds higher than the concentration of Pb ions reported in unfertilized ones. The mean concentrations of Pb in the root and shoot were 313 mgkg-1 and 46 mg kg-1 respectively with bioaccumulation and Transfer factor below 1.0. However, the rhizobium counts decreased as the pollution strength of the Pb ion increased. This study concluded that Vigna unguiculata immobilized Pb contaminants from the soil environment and that leguminous plants could be model plants for the treatment of Pb contaminated soil.